PENGARUH DIAPHRAGMATIC BREATHING DAN ENDURANCE EXERCISE TERHADAP PENINGKATAN KAPASITAS KARDIORESPIRASI PADA PASIEN HOSPITAL-ACQUIRED PNEUMONIA - Azzahra, Alifia; Puspitarani, Annisya; Sativani, Zahra; Pahlawi, Riza (UI Scholars Hub, 2022)
The purpose of this case study is to determine the effect of diaphragmatic breathing and endurance exercise in hospital-acquired pneumonia (HAP). Nosocomial pneumonia that occurs in 48 hours or more after the patient admitted to the hospital, without any signs of pulmonary infection. The existence of clinical manifestations that appear, patients with HAP tend to avoid physical activity which can decrease the functional capacity of the respiratory system and have an impact on decreasing endurance. Diaphragmatic breathing exercise is thought to be able to help reduce shortness of breath, reduce the work of the accessory muscles of breathing, improve breathing frequency and also improve breathing patterns. Endurance training aims to increase the stimulation of the cardiorespiratory system response so that oxygen transportation becomes more efficient and the patient is able to carry out optimal activities. Evidence-based case report is the method of this research, with a clinical question